In Utero Exposure to Mercury Is Associated With Increased Susceptibility to Liver Injury and Inflammation in Childhood. Issue 3 (30th August 2021) - Stratakis, Nikos; Golden‐Mason, Lucy; Margetaki, Katerina; Zhao, Yinqi; Valvi, Damaskini; Garcia, Erika; Maitre, Léa; Andrusaityte, Sandra; Basagana, Xavier; Borràs, Eva; Bustamante, Mariona; Casas, Maribel; et al.
Abstract : Background and Aims: Nonalcoholic fatty liver disease (NAFLD) is the most prevalent cause of liver disease in children. Mercury (Hg), a ubiquitous toxic metal, has been proposed as an environmental factor contributing to toxicant‐associated fatty liver disease. Approach and Results: We investigated the effect of prenatal exposure to Hg on childhood liver injury by combining epidemiological results from a multicenter mother–child cohort with complementary in vitro experiments on monocyte cells that are known to play a key role in liver immune homeostasis and NAFLD. We used data from 872 mothers and their children (median age, 8.1 years; interquartile range [IQR], 6.5‐8.7) from the European Human Early‐Life Exposome cohort. We measured Hg concentration in maternal blood during pregnancy (median, 2.0 μg/L; IQR, 1.1‐3.6). We also assessed serum levels of alanine aminotransferase (ALT), a common screening tool for pediatric NAFLD, and plasma concentrations of inflammation‐related cytokines in children. We found that prenatal Hg exposure was associated with a phenotype in children that was characterized by elevated ALT (≥22.1 U/L for females and ≥25.8 U/L for males) and increased concentrations of circulating IL‐1β, IL‐6, IL‐8, and TNF‐α. Consistently, inflammatory monocytes exposed in vitro to a physiologically relevant dose of Hg demonstrated significant up‐regulation of genes encoding these four cytokines and increased concentrations of IL‐8 and TNF‐α in the supernatants. Conclusions: These findings suggest that developmental exposure to Hg can contribute to inflammation and increased NAFLD risk in early life.